Sequestering the 5′-cap for viral RNA packaging - Ding, Pengfei; Summers, Michael (Wiley, 2022)
Manyvirusesevolvedmechanismsforcappingthe5′-endsoftheirplus-strandRNAsasameansofhijackingtheeukaryoticmessengerRNA(mRNA)splicing/translationmachinery. Although capping is critical for replication, the RNAs of these viruseshave other essential functions including their requirement to be packaged aseither genomes or pre-genomes into progeny viruses. Recent studies indicate thathumanimmunodeficiencyvirustype-1(HIV-1)RNAsaresegregatedbetweensplic-ing/translation and packaging functions by a mechanism that involves structuralsequestration of the 5′-cap. Here, we examined studies reported for other virusesand retrotransposons that require both selective packaging of their RNAs and 5′-RNA capping for host-mediated translation. Our findings suggest that viruses andretrotransposons have evolved multiple mechanisms to control 5′-cap accessibility,consistentwiththehypothesisthatremovalorsequestrationofthe5′capenablespackageableRNAstoavoidcapturebythecellularRNAprocessingandtranslationmachinery.